2007
DOI: 10.1176/ajp.2007.164.5.789
|View full text |Cite
|
Sign up to set email alerts
|

Medication Access and Continuity: The Experiences of Dual-Eligible Psychiatric Patients During the First 4 Months of the Medicare Prescription Drug Benefit

Abstract: The findings indicate consequential medication access problems for psychiatric patients during the implementation of Medicare Part D. Although Centers for Medicare and Medicaid Services policies were enacted to ensure access to protected classes of psychopharmacologic medications, the high rates of medication access problems observed indicate further refinement of these policies is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…For example, a survey of psychiatrists showed that while most psychiatrists (77%) would accept new self-pay patients, only 44% would accept a new Medicaid patient and this rate was even lower for psychiatrists who were white, board certified, or graduates of US medical schools (Wilk et al 2005). As an example of how a PBRN can respond to emerging policy changes, the PBRN was used to assess psychotropic medication access and continuity in the first 4 months of the implementation of Medicare Part D’s prescription drug benefit (West et al 2007). Psychiatrists reported that 10% of eligible patients seen by psychiatrists experienced improved medication access, but that 18% of medically stable patients were required to change medications, 22% discontinued or temporarily stopped taking a medication due to coverage or management issues, and that 27% of these patients experienced a significant clinical adverse event as a result.…”
Section: Pbrns Within Mental Healthmentioning
confidence: 99%
“…For example, a survey of psychiatrists showed that while most psychiatrists (77%) would accept new self-pay patients, only 44% would accept a new Medicaid patient and this rate was even lower for psychiatrists who were white, board certified, or graduates of US medical schools (Wilk et al 2005). As an example of how a PBRN can respond to emerging policy changes, the PBRN was used to assess psychotropic medication access and continuity in the first 4 months of the implementation of Medicare Part D’s prescription drug benefit (West et al 2007). Psychiatrists reported that 10% of eligible patients seen by psychiatrists experienced improved medication access, but that 18% of medically stable patients were required to change medications, 22% discontinued or temporarily stopped taking a medication due to coverage or management issues, and that 27% of these patients experienced a significant clinical adverse event as a result.…”
Section: Pbrns Within Mental Healthmentioning
confidence: 99%
“…[25] In a small national survey of 908 psychiatrists, about 15% reported that their dual-eligible patients with mental illness had difficulties accessing refills or new psychiatric prescriptions and 8% had to switch psychiatric medications due to coverage restrictions during the transitional period. [26] …”
Section: Overall Effectmentioning
confidence: 99%
“…[42] In a 2006 national survey of 1,490 psychiatrists who treated dual-eligible psychiatric patients, utilization management strategies employed in Part D plans were associated with elevated risk of medication access problems, such as medication discontinuation or temporary termination, and adverse medical events. [26] …”
Section: Utilization Management Toolsmentioning
confidence: 99%
“…These studies, conducted by the American Psychiatric Association’s (APA) Research Institute, provide an important look at the Part D program and its effect on dually-eligible beneficiaries with mental illness 7–10 . Psychiatrists have reported disruptions in access to medicine among dually-eligible beneficiaries, resulting in a troubling number of interactions with crisis services and inpatient hospitalizations 7 . Over 40 per cent of the dually-eligible patients reported on by their psychiatrists in these studies had experienced a medication access problem since the implementation of Part D.…”
Section: Literature Reviewmentioning
confidence: 99%